PENGARUH PELAYANAN KOPERASI SIMPAN PINJAM DALAM MENINGKATKAN PRODUKTIVITAS USAHA KECIL PASAR BECEK DI KABUPATEN TIGARAKSA PROPINSI BANTEN - Nurhadi Nurhadi (Universitas Bina Sarana Informatika, 2016)
The economy is structured as a joint venture based on the principle of kinship. with the globalization launched by the government following the signing of free trade, the fate of any co-faced with anxiety onslaught of foreign products. Like a